Entorno familiar y su incidencia en el aprendizaje en los estudiantes de la UE Juan E. Verdesoto, Babahoyo. 2022 - Escobar Castro, Eliana Paola (2023)
The family environment reflects an important role in the education of students, so it transmits values and principles that allow the student to perform in an educational environment, the objective of the investigation was to analyze the influence that parents have in the learning process in the academic formation of their children, the research was carried out based on a mixed approach, because the qualitative relationships of the interfering variables were observed and quantitatively when verifying the statistical data in relation to the number of individuals and their responses. Among the most relevant results, there is evidence of a limited incidence that the home has in academic life, this is due to different factors that interfere with the intervention of family members in their academic training. The relationship of the family environment with student learning is given through family participation, so in this development there must be shared responsibility in order to achieve good communication with the teacher, in this way it is possible to have firmness with the student